A bipartite separable ball and its applications. (4th February 2015) - Shen, Shu-Qian; Li, Ming; Li, Lei
Abstract: In this paper, based on a matrix norm, we first present a ball of separable un-normalized states around the identity matrix for the bipartite quantum system, which is larger than the separable ball in Frobenius norm. Then the proposed ball is used to get not only simple sufficient conditions for the separability of pseudopure states and the states with strong positive partial transposes, but also a separable ball centered at the identity matrix for the multipartite quantum system.